Hubungan Nomophobia Dengan Konsentrasi Belajar pada Mahasiswa S1 Keperawatan Stikes Payung Negeri Pekanbaru - Desti Puswati; Nadia Putri Sari (STIKes Payung Negeri Pekanbaru, 2021)
During Covid-19 pandemic, learning process was carried out online so that most students relied heavily on devices for online learning that were easy to carry anywhere, namely smartphones. the development of smartphone technology, which rapidly increasing, facilitated all activities and making individuals, especially students, feel anxious when away from smartphones. this incident is called nomophobia. normophobia can interfere with learning concentration. The research was carried out at the Stikes Payung Negeri Pekanbaru. based on the results of interviews which was conducted with 10 students; 7 students (70%) said they felt fear, anxiety, and their learning concentration was disturbed when away from their cellphones. The purpose of this study was to examine the relationship between nomophobia and learning concentration in undergraduate students of STIKes Payung Negeri Pekanbaru. This study used a stratified random sampling technique with a sample of 133 respondents. Correlation research design with cross sectional approach. The instrument in the form of a nomophobia questionnaire was taken from various sources and was tested for validity at the D3 Nursing Stikes Payung Negeri Pekanbaru. The results of the study were high normophobia 60.2% and low learning concentration 48.9%. P-value 0.00 where =0.05 means p<α so that the alternative hypothesis (Ha) fails to be rejected, which means that there is a relationship between Nomophobia and the level of concentration in students' learning.